English Learning Management System (ELMS) in the post-pandemic era: Comparative study - Junining, Esti; Herawati; Setiarini, Nuria (Universitas Muhammadiyah Sidoarjo, 2024)
In the post-pandemic era, virtual English educational environments are replacing the role of traditional classroom instruction. Due to the technological revolution and the COVID-19 pandemic, English learning has evolved considerably in recent decades in educational parties at the higher education levels in Indonesia, especially English Language Teaching, have offered various new options. ELMS is referred to as a program that may optimize the ease of English learning while promoting sustainable learning at home, particularly for lecturers who must provide English teaching-learning during the challenging periods of the COVID-19 pandemic. Existing previous studies confirmed that acceptance of the ELMS in higher education may vary from one country to another. This paper attempted to answer questions dealing with students’ engagement in learning and the usage of ELMS in Indonesia compared to other countries. The study surveys online polling and measures their acceptance and preference of ELMS in Indonesian higher education. The findings showed that as a sustainability program in higher education, ELMS had favorable impacts during the COVID-19 outbreak and was recognized as user-friendly. HIGHLIGHTS: An English Learning Management System (ELMS) is a platform designed to facilitatethe teaching and learning of the English language. This research compares the use of ELMS in four continents namely Asia, Europe, Americaand Middle East There is no big difference of the use of ELMS in post-pandemic eras